1996
DOI: 10.1111/j.1432-1033.1996.00772.x
|View full text |Cite
|
Sign up to set email alerts
|

Ole e 3, An Olive‐Tree Allergen, Belongs to a Widespread Family of Pollen Proteins

Abstract: An allergen has been isolated from a saline extract of olive tree (Olea europaea) pollen. The protein consists of a single polypeptide chain of 9.2-kDa, as determined by mass spectrometry. It contains neither tryptophan nor tyrosine residues, and displays an acidic isoelectric point. The secondary structure of the protein, estimated from the analysis of the circular-dichroism spectrum in the peptide-bond region, is composed of 52% a-helix, 10% a-strand, 29% Sturn and 9% non-regular conformation. The N-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 40 publications
4
115
0
Order By: Relevance
“…This linkage is highly conserved among diverse species. In addition to the Brassica proteins, highly related pollen allergens have been identified in Betula verrucosa (Engel et al, 1997;Twardosz et al, 1997), Olea europaea (Batanero et al, 1997), Artemisia vulgaris (Engel et al, 1997), and the monocots Cynodon dactylon (Suphioglu et al, 1997), Phleum pratens, and Lilium longiflorum (Engel et al, 1997;Twardosz et al, 1997). The present study also describes cloning of APC1, a homolog from Arabidopsis, and demonstrates the presence of related sequences in Antirrhinum but not in tobacco (Nicotiana tabacum).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…This linkage is highly conserved among diverse species. In addition to the Brassica proteins, highly related pollen allergens have been identified in Betula verrucosa (Engel et al, 1997;Twardosz et al, 1997), Olea europaea (Batanero et al, 1997), Artemisia vulgaris (Engel et al, 1997), and the monocots Cynodon dactylon (Suphioglu et al, 1997), Phleum pratens, and Lilium longiflorum (Engel et al, 1997;Twardosz et al, 1997). The present study also describes cloning of APC1, a homolog from Arabidopsis, and demonstrates the presence of related sequences in Antirrhinum but not in tobacco (Nicotiana tabacum).…”
mentioning
confidence: 80%
“…In addition to the demonstration of homologous sequences in Antirrhinum described here, related proteins have been identified in Betula verrucosa (Engel et al, 1997;Twardosz et al, 1997), Olea europaea (Batanero et al, 1997), Artemisia vulgaris (Engel et al, 1997), Cynodon dactylon (Knox et al, 1992), Phleum pratense, and Lilium longiflorum (Engel et al, 1997;Twardosz et al, 1997), and multiple types were identified in Brassica rapa and B. napus (Toriyama et al, 1995;Lim et al, 1996) during the course of this study. The partial amino acid sequence from the second pollen protein purified in this study, PP-A, indicates that it, too, is a member of this protein family.…”
Section: Discussionmentioning
confidence: 99%
“…91 Polcalcin accumulation at the tip of growing pollen tubes 18,24,25 suggests a correlation with the tipfocused Ca 2þ gradient which determines the direction of pollen tube growth. 10,18,19,21,23 -26 The polcalcins are rapidly washed out of the cytosol upon pollen hydration, 10,13,18,19,24,25,27 which explains the allergenicity of the intracellular polcalcins. Although the polcalcins are minor allergens in terms of IgE binding prevalence, human basophil histamine release assays and skin prick tests revealed remarkable allergenic potency in affected patients.…”
Section: Introductionmentioning
confidence: 99%
“…9 Between 5% and 20% of birch pollinotics mount IgE antibodies against the 9.4 kDa minor birch pollen allergen Bet v 4, an acidic two EF-hand Ca 2þ -binding polcalcin. 10,11 A series of allergenic polcalcins have been reported in the literature, namely Aln g 4 from alder (Alnus glutinosa), 12 Ole e 3 from olive (Olea europaea), 13,14 Syr v 3 from lilac (Syringa vulgaris; Ledesma et al, unpublished), Bra n 1 or BPC1 and Bra n 2 from oilseed rape (Brassica napus) as well as Bra r 1 and Bra r 2 from turnip rape (Brassica rapa), 15 -18 Phl p 7 from timothy grass (Phleum pratense), 19 and Cyn d 7 from Bermuda grass (Cynodon dactylon). 20,21 Aln g 4, Syr v 3, Bra n 1 or BPC1, Bra n 2, Bra r 1, Bra r 2 and Phl p 7 as well as the polcalcin APC1 from mouse-ear cress (Arabidopsis thaliana), 18 however, have not been included in the official allergen list of the International Union of Immunological Societies (IUIS) yet and the allergen designations Bra n 1 and Bra r 2 even conflict with two unrelated allergens.…”
Section: Introductionmentioning
confidence: 99%
“…The allergenic activity of polcalcins is primarily associated with the Ca 2+ -bound isoforms (Engel et al 1997, Hayek et al 1998& Twardosz et al 1997. The prevalence of Ole e 3 is higher than 50% of the olive pollen sensitized population (Batanero et al 1996a). This allergen shows polymorphism at positions 43 (L  P) and 80 (V  I) of its amino acid sequence (Ledesma et al 1998b).…”
Section: Polymorphism Of Olive Pollen Allergensmentioning
confidence: 99%